PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN LUDO PADA MATERI HIDROKARBON - Pratiwi, Vika; Jayanti, Etrie; Nurlaila, Nurlaila (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2025)
This study is a type of R&D (research and development) research aimed at developing an appropriate ludo game- based learning medium for hydrocarbon material and to find out the practicality of using this ludo game as a chemistry learning medium for hydrocarbon material. The development model used is the ADDIE development model, which is used up to the development stage. The validators in this study consisted of material expert validators, media experts, and education practitioners. The subjects in this study were students of class XI-MIA at one of the MA in Ogan Ilir district consisting of 4 students in the one-to-one trial, and 18 students in the small group trial. Data collection used interviews, validation sheets, and questionnaires. Based on the feasibility of the ludo game-based learning medium evaluated by the subject matter experts, the research results obtained a score of 80% with a "highly feasible" category and a score of 85% from educational practitioners with a "highly feasible" category. Validation by media experts received a score of 92,5%, also in the "highly feasible" category. The results of the one-to-one trial indicated a practicality percentage of 94,27%, categorized as "highly practical", and the small group trial results showed a percentage of 96,54%, also categorized as "highly practical".